The Economic Impact of Poor Road System on Agricultural Value Chain in Rivers State, Nigeria - Nathan Udoinyang (MultiTech Publisher, 2024)
The purpose of this research was to examine the economic impact of poor road system on agricultural value chain in Rivers State. This study utilized a survey methodology to collect data from the whole population of Rivers state. A total of 355 people from the three senatorial districts filled out the survey, and the researcher used the Taro Yamane formula to determine that a sample size of 400 was appropriate. With a mean criteria of 3.0, the Statistical Package for the Social Sciences (SPSS) were used to analyze the study's research topics. Reviewing the results of the economic impact of poor road network on agricultural value chain in Rivers State are; damage of perishable goods as a result of long hours spent in transporting the goods from farm to market, etc. The study concluded that good road system is one of the factors to achieve food sufficiency in the Rivers State and recommended that government of the state should assists farmers in conveying their farm produce to urban market where they are sold for better price by providing vehicles for them, create good road network that connect farmlands to modern market in urban areas of the state among others.